ADMINISTRATIVE AND LEGAL MECHANISMS OF PUBLIC CONTROL OVER THE IMPLEMENTATION OF ENVIRONMENTAL RIGHTS IN PRESENT-DAY UKRAINE - Krainii, Pavlo; Toronchuck, Ivan (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2023)
The purpose: to survey the Ukrainian normative-legal base that ensures the administration of public control over the implementation of citizens’ environmental rights under martial law in Ukraine. The methodological basis of the study has been developed with due regard to the issues of the scientific research, whereby the authors reveal certain administrative and legal forms of public participation in public control over the activities of public authorities, which guarantee the implementation of environmental rights. Results: it has been ascertained that in Ukraine, there are various forms of public control that allow the institutions of civil society to participate in the implementation of state policy aimed at protecting environmental rights in Ukraine under martial law. The article identifies those forms of control that require further development and improvement. Discussion: the already existing administrative and legal forms of public control over the implementation of citizens’ environmental rights have been determined at the legislative level. However, the ongoing war, the legal regime of martial law, and the adoption of new regulations require their revision. The article also considers the activities of advisory bodies under the Ministry of Ecology. The current public council operates within the respective Regulation. It has been outlined that such councils can become a rather effective administrative and legal form of public control. Their administrative and legal status makes it possible to expand their powers in order to use other forms of public control: public discussions, public hearings, and public expertise. The authors propose to take into consideration the possibility of adopting a separate Law of Ukraine “On Consultative and Advisory Bodies” to provide for the possibility of establishing the respective public councils not only within executive authorities but also within the bodies local self-government.